Twenty Years of Middle School STEM Camps at UW-La Crosse - Kelly, Susan E (Proceedings of the Wisconsin Space Conference, 2019)
UW-La Crosse has offered middle school science and mathematics camps for twenty years through a partnership of its College of Science and Health and its Office of Continuing Education and Extension. This paper will give information on the history of the program, overall camp design, specific examples of workshop offerings, and details on the administration of the programs.